O corte da sexualidade: o ponte de viragem da psiquiatria brasileira no século XIX - Beluche, Renato (2006)
During the last quarter of the nineteenth century, Brazilian psychiatry has based its speeches on sexuality. It became the main element in the classification/institution of deviant identities after 1870, in the period of the Empire decline. The appearance of the so called new ideas and the anti-slavery measures created fears of the black population understood as a social danger that lead to a new way of comprehension of Brazilian society and its deviant identities. These theories about social deviance have used sexuality as one of the strategies that made possible the critique of the old imperial order and the consolidation of the bourgeois one as well. The objective was to avoid social change keeping social inequalities and hierarchies from the past.